Immunoprofiling of monocytes in STAT1 gain-of-function chronic mucocutaneous candidiasis - Bloomfield, Marketa; Zentsova, Irena; Milota, Tomas; Sediva, Anna; Parackova, Zuzana (Frontiers in Immunology, 2022)
Patients with STAT1 gain-of-function (GOF) mutations suffer from an inborn error of immunity hallmarked by chronic mucocutaneous candidiasis (CMC). The pathogenesis behind this complex and heterogeneous disease is still incompletely understood. Beyond the well-recognized Th17 failure, linked to the STAT1/STAT3 dysbalance-driven abrogation of antifungal defense, only little is known about the consequences of augmented STAT1 signaling in other cells, including, interestingly, the innate immune cells. STAT1-mediated signaling was previously shown to be increased in STAT1 GOF CD14+ monocytes. Therefore, we hypothesized that monocytes might represent important co-orchestrators of antifungal defense failure, as well as various immunodysregulatory phenomena seen in patients with STAT1 GOF CMC, including autoimmunity. In this article, we demonstrate that human STAT1 GOF monocytes are characterized by proinflammatory phenotypes and a strong inflammatory skew of their secretory cytokine profile. Moreover, they exhibit diminished CD16 expression, and reduction of classical (CD14++C16-) and expansion of intermediate (CD14++16+) subpopulations. Amongst the functional aberrations, a selectively enhanced responsiveness to TLR7/8 stimulation, but not to other TLR ligands, was noted, which might represent a contributing mechanism in the pathogenesis of STAT1 GOF-associated autoimmunity. Importantly, some of these features extend to STAT1 GOF monocyte-derived dendritic cells and to STAT1 GOF peripheral myeloid dendritic cells, suggesting that the alterations observed in monocytes are, in fact, intrinsic due to STAT1 mutation, and not mere bystanders of chronic inflammatory environment. Lastly, we observe that the proinflammatory bias of STAT1 GOF monocytes may be ameliorated with JAK inhibition. Taken together, we show that monocytes likely play an active role in both the microbial susceptibility and autoimmunity in STAT1 GOF CMC.